EFFECTIVENESS OF FISCAL AND MONETARY POLICY IN SUPPRESSING INFLATION RATE IN TRI COUNTRIES (TURKEY, RUSSIA, INDONESIA) - Og'lu, Ahmed Muaz Yakup; Harahap, Abdi Syahrial (International Proceeding of Law and Economic, 2020)
The purpose of this study is to determine the effect of fiscal and monetary policy variables on Inflation in Turkey, Russia and Indonesia. The variables used in this study are Inflation, Exchange Rate, Money Supply, Gross Domestic Product, Taxes and Government Spending. The method used is Panel ARDL. The results showed that in overcoming Inflation, Turkey, Russia and Indonesia used the Variables of Money Supply and Taxes. But in the panel it turns out that the amount of money in circulation and taxes are also able to be a leading indicator to overcome inflation in Turkey, Russia and Indonesia, but its position is not stable in the short run and long run. While the main Leading indicator in overcoming Inflation in Turkey, Russia and Indonesia is Gross Domestic Product and its position is stable when viewed from the short run and long run. Thus it is recommended to the Central Bank in each country Turkey, Russia and Indonesia to take monetary policy through the Money Supply. It is recommended to the government through fiscal policy, namely Government Expenditure to encourage exchange rate stability and efforts to increase Gross Domestic Product to accelerate growth in the short and long term.